Challenges to Political Cosmopolitanism: The Impact of Racialised Discourses in Post-Apartheid South Africa - Hana Horáková (Modern Africa)
One of the key challenges of post-apartheid South Africa has been the need to create a South African “nation.” The efforts of the leading African National Congress started with Nelson Mandela’s reconciliatory discourse of a “rainbow nation,” via Thabo Mbeki’s concept of the African Renaissance, to the current stream of racial nationalism articulated as “Africanisation.” The present article attempts to examine the dilemma which the ANC as the major custodian of nation-building has been facing since the 1990s: how to reach a balance between a civic nationalism based on cosmopolitan values and the need to redress the legacy of apartheid and persisting racial inequalities. It is argued that the current culturalist discourse of Africanisation is not only contentious but also dangerous for the cohesion of the fragile democratic society of post-apartheid South Africa.